Address resolution protocol optimization - J.L.Tai,; Nor Adnan Yahaya,; K. Daniel Wong, (2009)
This paper proposes an improved Address Resolution Protocol (ARP) for Ethernet-based networks. In the proposed alternative method, the ARP request packets are not broadcasted but instead unicasted to an ARP server which will have all the <ip, MAC> mappings of all the hosts connected to the network. This significantly reduces ARP signaling and processing overhead. The ARP server obtains the mappings through a novel passive method that does not introduce additional overhead in the network. Furthermore, the use of the ARP server makes it much easier to secure the network against certain attacks like ARP poisoning.